Bacterial Enteropathogens Isolated in Childhood Diarrhoea in Kuala Lumpur - The Changing Trend - Lee, W.S.; Puthucheary, S.D. (2002)
A retrospective review of all stool samples obtained from children aged <16 years with diarrhoea from University of Malaya Medical Centre (UMMC), Kuala Lumpur, from 1978 to 1997 was undertaken to ascertain the pattern of bacterial pathogens causing diarrhoea in children in an urban area in Malaysia.